Factors influence marketing strategies for company's brand: a study from Konsvltan Sdn.Bhd./ Nor Najihah Mohd Alias - Mohd Alias, Nor Najihah (2018)
This study was carried out to find out the factors influencing in creating marketing strategies for company brand. A total of 50 questionnaires was given out to consumer at a shopping centre from a star of Avenue K Kuala Lumpur. The respondent are picked randomly which is choose randomly by researcher in order to gain data from the respondent The date were collected by a questionnaires that distributed to respondents. The questionnaires was designed to get the primary data about the factors influencing in creating marketing strategies for company’s brand. Basically, in this study have independent variables which are endorser credibility and brand credibility. Based the data analysis from the study carried out, factors influence marketing strategy influenced by endorser credibility factor While brand credibility does not achieve the marketing strategy. This is because, based on the correlation table shows that endorser credibility obtained a high correlation value which is the 0.801. Hence, the factor that support this study Is endorser credibility Which influence the marketing strategies for company's brand. By using in marketing strategies can help business success in future. The findings for this study is supported in journal Celebrity endorsement, brand credibility and brand equip (Amanda Spry et,. 2011) Which the result is same where it can sad that celebrity endorser can give impact towards brand.